The Confluence of Nanotechnology and Heat Shock Protein 70 in Pioneering Glioblastoma Multiforme Therapy: Forging Pathways Towards Precision Targeting and Transformation - Amrita Arup Roy; Abhijeet Pandey; Namdev Dhas; Manasa Manjunath Hegde; Harendra S. Parekh; Sai Balaji Andugulapati; Krishnadas Nandakumar; Bola Sadashiva Satish Rao; Srinivas Mutalik (Advances in Pharmacological and Pharmaceutical Sciences)
Trial Registration: ClinicalTrials.gov identifier: NCT00054041 and NCT04628806